2002
DOI: 10.1017/s1357729800053145
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth response in pigs, muscle protein turn-over and meat texture: effects of restriction/realimentation period

Abstract: The present experiment was designed to evaluate the effect of different time spans of ad libitum feeding of pigs prior to slaughter after a period of restricted feeding on performance and texture characteristics of the meat. Te n litters of five pigs (Duroc ✕ Landrace ✕ Large White crosses) were allocated to five feeding treatments (AA, R28A42, R43A27, R52A18 and R60A10) at the age of 70 days. AA-pigs were given ad libitum a concentrate diet from day 70 to slaughter at day 140 (approx. 100 kg live weight). R28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
56
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 35 publications
15
56
3
2
Order By: Relevance
“…In this study, IMF content in R pigs was lower than A pigs during the restriction period and slightly lower after refeeding for 2 days; however, there was no difference after full compensation. Therefore, compensatory growth appeared to modify carcass composition by increasing fat deposition, as indicated by the IMF weight reaching the same level as the control in the subsequent re-alimentation period, in agreement with Donker et al (1986), Therkildsen et al (2002), Kristensen et al (2004) and Heyer and Lebret (2007) who reported that IMF and/or back fat thickness were not different after refeeding.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this study, IMF content in R pigs was lower than A pigs during the restriction period and slightly lower after refeeding for 2 days; however, there was no difference after full compensation. Therefore, compensatory growth appeared to modify carcass composition by increasing fat deposition, as indicated by the IMF weight reaching the same level as the control in the subsequent re-alimentation period, in agreement with Donker et al (1986), Therkildsen et al (2002), Kristensen et al (2004) and Heyer and Lebret (2007) who reported that IMF and/or back fat thickness were not different after refeeding.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, as a proportion of carcass weight LD muscle of R pigs showed slightly higher value than A pigs at SL1 and SL2 (the absolute wet weight of the muscle was not significantly different at these points nor at SL3; data not shown), but this muscle was not different at SL3, suggesting that compensatory growth had no effect on muscle tissue weight but did influence internal organs. Overall, these results indicate that the compensatory growth during the re-alimentation period occurred due to increased internal organ weight and fat deposition in accordance with Mersmann et al (1987), Bikker et al (1996) and Therkildsen et al (2002 and. In this study, IMF content in R pigs was lower than A pigs during the restriction period and slightly lower after refeeding for 2 days; however, there was no difference after full compensation.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Contudo, os resultados encontrados neste estudo corroboram os reportados por Barbosa et al (2002a,b), que aplicaram níveis de 5 a 15% de restrição com 2.083 e 2.252 kcal de energia líquida (EL) na dieta e também não Tabela 2 -Desempenho de suínos submetidos a quatro programas de restrição alimentar Therkildsen et al (2002), aplicando 40% de restrição alimentar no período dos 70 aos 140 dias de idade, observaram ao abate (100 kg PC) espessuras de toucinho semelhantes à dos animais sem restrição alimentar (Tabela 5).…”
Section: Resultsunclassified